MFIs and their Impact on Capacity Building of SHGs Members MFIs and their Impact on Capacity Building of SHGs Members - Dr. Suman Kalyan Chaudhury (Srusti Management Review, 2014)
Microfinance has been treated as an important tool for economic development. Microfinance lenders offer small loans to aspiring as well as current business owners. These loans assist people in getting access to traditional financing and offer jobs to local communities. The size of microfinance loan may vary from lender to lender. But it plays vital role in economic development through job creation, financial stability and global poverty. Microfinance encompasses the provision of financial services and the management of small amounts of money through a range of products and a system of intermediary functions that are targeted at low income clients. In this paper the authors tries to highlight MFIs and their impact on capacity building of SHGs.